Uma proposta de catálogo de obras para contrabaixo de Edmundo Villani-Côrtes - Porto, José Pedro Guimarães (2020)
This research aims at cataloging the Brazilian composer Edmundo Vilanni-Côrtes’ works for double bass. The research used data collection based on exploratory/descriptive investigation; bibliographic and documentary research; and an interview with the composer. To this end, the research draws in interdisciplinarity areas of knowledge, such as Librarianship and Information Science, to inform a theoretical and technical framework to present the data and guide the development of the proposed catalog, using the conceptual model Functional Requirements for Bibliographic Records (1998, 2008) considering authors who discuss such model. A catalog of works is proposed at the end, comprising a presentation and a bibliographic record for each work, including the musical incipt.